Interrelationships Among Dissertation Writing Challenges: A Correlational Study of Moroccan Doctoral Students - Dardour, Majid (International Journal of Language and Literary Studies, 2026)
Doctoral dissertation writing involves a complex interplay of academic, methodological, systemic, and personal demands that collectively influence doctoral progress and completion. Drawing on data from 300 doctoral candidates enrolled in English Studies across ten Moroccan universities, this correlational study builds on prior descriptive research to examine the interrelationships among dissertation-writing challenges. Four domains were investigated: barriers to effective academic writing, difficulties in literature review and scholarly argumentation, challenges related to research planning and methodological rigor, and systemic and personal obstacles. Given the non-normal distribution of the data, Spearman’s rank-order correlation coefficients (?) were employed to assess the strength and direction of relationships among these domains. The findings reveal strong, positive, and statistically significant correlations across all categories, indicating that dissertation-writing challenges tend to co-occur and mutually reinforce one another rather than operate as isolated difficulties. Notably, systemic and personal obstacles show particularly strong associations with academic writing and methodological challenges. These results underscore the systemic and interconnected nature of doctoral dissertation difficulties and highlight the need for integrated, holistic doctoral support strategies that simultaneously address academic, structural, and personal dimensions of doctoral education.